2002
DOI: 10.1110/ps.5060102
|View full text |Cite
|
Sign up to set email alerts
|

Role of water in the catalytic cycle of E. coli dihydrofolate reductase

Abstract: Dihydrofolate reductase (DHFR) catalyzes the nicotinamide adenine dinucleotide phosphate (NADPH)-dependent reduction of 7,8-dihydrofolate (H 2 F) to 5,6,7,8-tetrahydrofolate (H 4 F). Because of the absence of any ionizable group in the vicinity of N5 of dihydrofolate it has been proposed that N5 could be protonated directly by a water molecule at the active site in the ternary complex of the Escherichia coli enzyme with cofactor and substrate. However, in the X-ray structures representing the Michaelis complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 41 publications
4
51
0
Order By: Relevance
“…Although no water molecule could be observed in the X-ray structure representing the Michaelis complex of the E. coli enzyme, energy minimization calculations revealed that water could be placed in hydrogen bonding distance of N-5 with only minor conformational changes in DHFR. 49 No ionizable group in the vicinity of N-1′ of the modelled DAROPP could be found in the proposed active site of MjaRED. In anology to the DHFR reaction, a water molecule could also act as a direct proton donor of N-1′.…”
Section: Discussionmentioning
confidence: 95%
“…Although no water molecule could be observed in the X-ray structure representing the Michaelis complex of the E. coli enzyme, energy minimization calculations revealed that water could be placed in hydrogen bonding distance of N-5 with only minor conformational changes in DHFR. 49 No ionizable group in the vicinity of N-1′ of the modelled DAROPP could be found in the proposed active site of MjaRED. In anology to the DHFR reaction, a water molecule could also act as a direct proton donor of N-1′.…”
Section: Discussionmentioning
confidence: 95%
“…While extensive research has shown that the proton source in the EcDHFR‐catalysed reaction is most likely the solvent itself (see refs. 9, 15, 16, and references therein) this question has not been addressed in TmDHFR.…”
Section: Comparison Of Wild‐type Tmdhfr and Its R28k And R28q Variantsmentioning
confidence: 99%
“…[60] More recent molecular-dynamics (MD) calculations propose the reverse sequence. [61] Other factors have been proposed to facilitate catalysis. A positive electrostatic potential around the active site of Ec DHFR might steer binding of the negatively charged substrate and cofactor.…”
Section: E Coli Chromosomal Dhfrmentioning
confidence: 99%